1983
DOI: 10.1115/1.3241015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Entrained Air on the Performance of a Horizontal Axial-Flow Pump

Abstract: The performance of an axial-flow pump was investigated under air-admitting conditions and the results were compared with those obtained for radial-flow pumps investigated in our previous studies. For the axial-flow pump we measured head as a function of impeller speed, liquid flow rate, and air void fraction. Flow visualization was performed and we correlated air bubble size as a function of Weber number based on mean impeller velocity. Overall flow patterns and the locations of air coalesence within the impel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…In this case the critical inlet volumetric quality is only about β = 3% or 4% and the degradation appears to occur at lower volume fractions for lower flow coefficients. Murakami and Minemura (1978) obtained similar data for both axial and centrifugal pumps, though the performance of axial flow pumps appear to fall off at even lower air contents.…”
Section: Multiphase Flows In Pumpssupporting
confidence: 63%
See 1 more Smart Citation
“…In this case the critical inlet volumetric quality is only about β = 3% or 4% and the degradation appears to occur at lower volume fractions for lower flow coefficients. Murakami and Minemura (1978) obtained similar data for both axial and centrifugal pumps, though the performance of axial flow pumps appear to fall off at even lower air contents.…”
Section: Multiphase Flows In Pumpssupporting
confidence: 63%
“…Below this critical value, the homogeneous theory works well; larger volumetric qualities of air produce substantial degradation in performance. Patel and Runstadler (1978), Murakami and Minemura (1978) and many others present similar data for pumps ingesting air/water and steam/water mixtures. Figure 8.17 presents another example of the air/water flow through a centrifugal pump.…”
Section: Multiphase Flows In Pumpsmentioning
confidence: 49%
“…This type of flow occurs in piping systems of several industrial areas such as nuclear power plants, petroleum industries or sewage pipelines. The presence of air in such facilities is usually unwanted as it may induce for instance pressure surges and traveling air pockets, leading to reduced efficiency and damages for pumping systems, see [33,35] ; an accurate modeling is thus necessary to improve performances and reliability. Although being studied since many years, the macroscopic description of those flows is still complex to assess as they may display different regimes such as dispersed flow, stratified flow, pressurized flow (pipe full of water), slug flow and transitions between them, see [29] for details.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering studies by Denny (1956) revealed that a mere 1% air volume into the pump's suction line through air-entraining vortices can reduce a centrifugal pump's efficiency up to 15%. Other studies show that air volumes greater than 3% significantly reduces pump performance, and in extreme conditions, damages mechanical components (Murakami and Minemura 1983;Patel and Runstadler 1978;Florajancic 1970). Hence, to prevent air entrainment at intakes, a critical submergence (Sc), at which air entrainment would begin, should be determined.…”
Section: Preventing Air Admissionmentioning
confidence: 98%